Peran Intrapreneurship dalam Membangun Daya Saing Kultural di Perguruan Tinggi: Sebuah Kerangka Penelitian - Agustinus Dedy Handrimurtjahjo (Binus Business Review, 2012)
This paper develops a conceptual framework for intended study which will examine the role of intrepreneurship in building cultural competitiveness in Higher Education (HE). Intrapreneurship (entrepreneurship within existing organizations) is used on organizational level. Previous study argued that four variables of Cultural Competitiveness (entrepreneurship, innovativeness, market orientation, and organizational learning) had a direct effect on organizational performance. Meanwhile, the other study argued that Intrapreneurship had a direct effect on organizational performance. The effect of the four market-based elements (intrapreneurship, market orientation, innovativeness and organizational learning) on performance will be examined by testing two alternative analytical models in different types of higher education institutions. The size and age of HE institutions are also considered as the interactive elements that might be different across different HE institutions. Testing two alternative models in developing countries will support whether the generalizability of the two alternative models and the constructs used in different country setting is acceptable.